Unravelling urban advantages - A meta-analysis of agglomeration economies - Stuart Donovan; Thomas de Graaff; Henri de Groot; Carl Koopmans (Tinbergen Institute, 2021)
A large body of literature considers the productive advantages of cities, or "agglomeration economies". Most empirical studies report positive agglomeration economies, although large variation exists in the magnitude of estimates. We use a meta-analysis to explore this variation, drawing on 6,684 estimates from 295 studies that cover 54 countries and span six decades. Using rich data and robust methods, we unify and extend earlier reviews. For our preferred combination of study attributes, we find agglomeration elasticities are likely to lie in the range 2.7–6.4%. Our findings confirm the controls enabled by detailed data give rise to smaller estimates. We also document several trends, with overall estimates rising from 1980–2000 and then falling. Estimates for manufacturing sectors, in contrast, fell for the entire six decades covered by our data. We speculate on possible causes of these trends, such as urban congestion, technological shocks, freight costs, and regulatory settings.
Keywords: R12; C11; R11; 330; agglomeration; meta-analysis; urbanisation; cities; productivity